The Serological and Virological Investigation of Canine Adenovirus Infection on the Dogs. (24th September 2013) - Bulut, Oya; Yapici, Orhan; Avci, Oguzhan; Simsek, Atilla; Atli, Kamil; Dik, Irmak; Yavru, Sibel; Hasircioglu, Sibel; Kale, Mehmet; Mamak, Nuri
Abstract : Two types of Canine Adenovirus (CAVs), Canine Adenovirus type 1 (CAV-1), the virus which causes infectious canine hepatitis, and Canine Adenovirus type 2 (CAV-2), which causes canine infectious laryngotracheitis, have been found in dogs. In this study, blood samples taken from 111 dogs, which were admitted to the Internal Medicine Clinic of Selcuk University, Faculty of Veterinary Medicine, with clinical symptoms. Seventy-seven dogs were sampled from Isparta and Burdur dog shelters by random sampling, regardless of the clinical findings. Dogs showed a systemic disease, characterized by fever, diarrhea, vomiting, oculonasal discharge, conjunctivitis, severe moist cough, signs of pulmonary disease and dehydration. Two dogs had corneal opacity and photophobia. In serological studies, 188 serum samples were investigated on the presence of CAV antibodies by ELISA. Total 103 (103/188–54.7%) blood samples were detected to be positive for CAV antibodies by ELISA. However, 85 (85/188–45.2%) blood samples were negative. Blood leukocyte samples from dogs were processed and inoculated onto confluent monolayers of MDCK cells using standard virological techniques. After third passage, cells were examined by direct immunoflourescence test for virus isolation. But positive result was not detected. In conclusion, this study clearly demonstrates the high prevalence of CAV infection in dogs.